Referral Patterns for Infertile Men: Predictors of Continued Treatment by Reproductive Endocrinologist versus Referral to a Nearby Urologist. Issue 4 (19th July 2022) - Shabto, Julie M.; Patil, Dattatraya; Poulose, Katherine; Bennett, Mackenzie P.; Xiao, Angel X.; Hipp, Heather S.; Kawwass, Jennifer F.; Mehta, Akanksha
Abstract: Introduction: We evaluated fertility clinic management of male factor infertility, including patient education and referral for urological evaluation and care. Methods: Using 2015–2018 Centers for Disease Control and Prevention Fertility Clinic Success Rates Reports, 480 operative fertility clinics in the United States were identified. Clinic websites were systematically reviewed for content regarding male infertility. Structured telephone interviews of clinic representatives were performed to determine clinic-specific practices for management of male factor infertility. Multivariable logistic regression models were used to predict how clinic characteristics (geographic region, practice size, practice setting, in-state andrology fellowship, state-mandated fertility coverage, annual in vitro fertilization cycles and percentage of in vitro fertilization cycles for male factor infertility) were associated with reproductive endocrinologist physician management of male infertility and/or referral to a urologist. Results: We interviewed 477 fertility clinics and analyzed available websites (474). The majority of websites (77%) discussed male infertility evaluation, while 46% discussed treatment. Clinics that were academically affiliated, had an accredited embryo laboratory and referred patients to a urologist were less likely to have the reproductive endocrinologist manage male infertility (all p <0.05). Practice affiliation, practice size and website discussion of surgical sperm retrieval were the strongest predictors of nearby urological referral (all p <0.05). Conclusions: Variability in patient-facing education, and fertility clinic setting and size influence fertility clinics' management of male factor infertility.